Granzyme A Stimulates pDCs to Promote Adaptive Immunity via Induction of Type I IFN - Shimizu, Kanako; Yamasaki, Satoru; Sakurai, Maki; Yumoto, Noriko; Ikeda, Mariko; Mishima-Tsumagari, Chiemi; Kukimoto-Niino, Mutsuko; Watanabe, Takashi; Kawamura, Masami; Shirouzu, Mikako; Fujii, Shin-ichiro (Frontiers in Immunology, 2019)
Granzyme A (GzmA), together with perforin, are well-known for their cytotoxic activity against tumor or virus-infected cells. In addition to this cytotoxic function, GzmA stimulates several immune cell types and induces inflammation in the absence of perforin, however, its effect on the dendritic cell (DC) is unknown. In the current study, we showed that recombinant GzmA induced the phenotypic maturation of plasmacytoid DCs (pDCs) and conventional DCs (cDCs), but not their apoptosis. Particularly, GzmA made pDCs more functional, thus leading to production of type I interferon (IFN) via the TLR9-MyD88 pathway. We also demonstrated that GzmA binds TLR9 and co-localizes with it in endosomes. When co-administered with antigen, GzmA acted as a powerful adjuvant for eliciting antigen-specific cytotoxic CD8+ T lymphocytes (CTLs) that protected mice from tumor challenge. The induction of CTL was completely abolished in XCR1+ DC-depleted mice, whereas it was reduced to less than half in pDC-depleted or IFN-α/β receptor knockout mice. Thus, CTL cross-priming was dependent on XCR1+cDC and also type I IFN, which was produced by GzmA-activated pDCs. These results indicate that GzmA -stimulated pDCs enhance the cross-priming activity of cDCs in situ. We also showed that the adjuvant effect of GzmA is superior to CpG-ODN and LPS. Our findings highlight the ability of GzmA to bridge innate and adaptive immune responses via pDC help and suggest that GzmA may be useful as a vaccine adjuvant.